Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pasien Badan Penyelenggara Jaminan Sosial Di Rumah Sakit Umum Daerah Kabupaten Pangkep - Nuryanti, Sinta; Hakim, Lukman; Rahim, Samsir (Universitas Muhammadiyah Makassar, 2021)
This study aimed to obtain answers about the effect of service quality on BPJS Health Patient Satisfaction in Pangkep District Hospital. The population in this study were all BPJS registered patients who received services at the Pangkep District General Hospital as many as 13500 people for (2) two months. The sample used 70 people taken based on nonprobability sampling. This type of research was descriptive research and research instruments used (1) Observation (2) Questionnaire and (3) Documentation. Research data processing used descriptive statistics while the data analysis techniques used Percentage (%) and Regression Analysis. Through data processing the results obtained There was an influence between the variable Quality of Service on the variable BPJS Patient Satisfaction in Pangkep Regency general hospital by 80.7% and the rest was influenced by factors in the Pangkep District Hospital.